"Ni Rome, ni Moscou" : l'itinéraire des militants communistes libertaires de langue française à Montréal pendant l'entre-deux-guerres - Houle-Courcelles, Mathieu (Université Laval, 2020)
Keywords: Communistes; Socialistes

Marxisme Import/Export Ltd: Parti Pris, Partisans, décolonisation et communisme hétérodoxe - Lacroix, Michel; Lefort-Favreau, Julien (Mens, 2021)
issued: 2021-21-00
Keywords: Communistes; Idéologies; Parti Pris

Destination: demain - Barrieau, Pierre; Richard, Geneviève (Continuité, 2024)
issued: 2024-21-00
Keywords: Transport en commun

Des oeuvres qui transportent - Labrosse, Benoîte (Continuité, 2024)
issued: 2024-23-00
Keywords: Transport en commun

La ligne de métro No.3 (rouge) à Dorval/Line 3 (red) in Dorval - Raymond, Jean-Pierre (Héritage Dorval, 2024)
Keywords: Dorval; Transport en commun

Métro, direction conservation - Lévesque, Jonathan; Senese, Manuela (Continuité, 2024)
issued: 2024-21-00
Keywords: Patrimoine; Transport en commun

Les 50 ans de l'effondrement de la rue Wellington - Clairoux, Benoit (Les Argoulets, 2024)
Keywords: Rues; Transport en commun; Verdun

Jeanne Corbin (1906-1944): A Canadian Communist Militant in a Man's World - Lévesque, Andrée (The Palgrave handbook of communist women activists around the world, 2023)
Keywords: Communistes; Femmes

The National Federation of Labor Youth and the Candy Bar Kids: Radical Youth, Popular Protest, and the Red Scare in Postwar Canada - Guard, Julie (Labour / Le Travail, 2024)
issued: 2024-21-00
Keywords: Communistes; Enfants; Grèves

Jeanne Corbin (1906-1944): A Canadian Communist Militant in a Man’s World - Lévesque, Andrée (The Palgrave Handbook of Communist Women Activists around the World, 2023)
Keywords: Communistes; Femmes; Partis politiques

Le pont Royal-Albert, 1875-1876: histoire d'une bérézina sur fond de rivalités ferroviaires - Fougères, Dany (Revue d'histoire de l'Amérique française, 2022)
issued: 2022-24-00
Keywords: Chemins de fer; Grand Tronc; Ponts

Rails vers Dorval/Rails to Dorval - Smith, Douglas N.W (Héritage Dorval, 2024)
Keywords: Banlieue; Chemins de fer; Grand Tronc

The Changing of the Guard: Bartlett McLennean, Roy Wolvin, and the Leveraged Buyout of the Montreal Transportation Compagny, 1903-1921 - Salmon, M. Stephen (Montreal's Square Mile: the making and transformation of a colonial metropole, 2024)
Keywords: Golden Square Mile; Navigation

À la croisée des chemins : mise en place et implantation du réseau de télégraphe électrique canadien, 1846-1867 - Dumais-Gingras, Pierre (Université du Québec à Montréal, 2021)
Keywords: Téléphone

“The Severity of This Service…” Canadien Inland Mariners in the Early Post-Conquest Era, 1760 to 1817 - More, John David (Université Queen's, 2021)
Keywords: Guerre; Navigation

Retrouver les lieux de passages - Lebleu, Jacques (Au fil d'ABC / SHAC, Société d'histoire d'Ahuntsic-Cartierville, 2024)
Keywords: Ponts; Rivière des Prairies; Sault-au-Récollet

“Far From Uninteresting”: Getting to Know the St. Lawrence River at Montreal During the Construction of the Victoria Bridge - Braiden, Heather (Urban History Review/Revue d'histoire urbaine, 2022)
In northern cities like Montreal, Quebec, Canada, the winters are long, and the construction season is condensed. In the mid-nineteenth century, knowing the St. Lawrence River’s seasonal variations and local construction customs helped railway and bridge builders save time and frustration during the very short working seasons. In this article, I investigate how technical and quasi-technical communications generated during the construction of the Victoria Bridge (1854–1860) are a rich source of urban knowledge. By examining visual and textual evidence in The Construction of the Great Victoria Bridge in Canada, I demonstrate how representations of the construction process are a tangible medium through which practical experience and a personal way of knowing the urban landscape are mediated. I argue that everyday experience and tacit knowledge move between social worlds and inform how audiences know and understand the colonial city.
Keywords: Victoria (pont)

Les phares de Dorval et d'autres aides à la navigation sur le Lac Saint-Louis/The Dorval Lightouse and other navigation aids on Lake St. Louis - Nieuwendyk, Dick (Héritage Dorval, 2022)
Keywords: Navigation; Saint-Louis (lac)

John Elsdale Molson contre le chemin de fer Grand Tronc - Bur, Justin (Le Bulletin de la Société d'histoire Rosemont-Petite-Patrie, 2024)
Keywords: Chemins de fer; Grand Tronc; Rosemont

De la barge aux usines: les mécanismes de déchargement du charbon au canal de Lachine - Paquet, Lucie (Bulletin de l'AQPI, 2021)
issued: 2021-21-00
Keywords: Lachine (canal); Montreal Rolling Mills

Le pont-tunnel Louis-Hippolyte-La Fontaine : aux origines d'une infrastructure routière régionale - Gaudry, William (Université du Québec à Montréal, 2022)
Keywords: Autoroutes; Ponts; Tunnels

Nos autoroutes, un patrimoine? - Gagnon, Maurice (Continuité, 2024)
issued: 2024-21-00
Keywords: Autoroutes; Patrimoine

L'histoire du chemin du Roy, XVIII-XXᵉ siècles : étude historique d'une route, d'un symbole, d'un récit - Fortin-Dupuis, Simon (Université Laval, 2024)
Keywords: Routes

Tramway à Montréal-1861 à 1959 - Tessier, Stéphane (Il était une fois...Montréal-Nord, 2024)
issued: 2024-22-00
Keywords: Montreal Street Railway Company; Tramways

Soutien et entraide. Les mouvements coopératifs et communautaires du Plateau de 1970 à 2000 (Bulletin de la Société d'histoire du Plateau-Mont-Royal, 2021)
issued: 2021-24-00
Keywords: Clinique des citoyens de Saint-Jacques; Cyclisme; Groupes populaires; Logement; Plateau Mont-Royal; Quartiers

Une mesure d'origine britannique. Les barrières à péage à Outremont - Waché, Gabriel; Bizier, Hélène-Andrée (Mémoire vivante, 2023)
issued: 2023-21-00
Keywords: Outremont; Routes

La maison du jardinier/The gardener's house - Design NFA inc. (Héritage Dorval, 2024)
Keywords: Chemins de fer; Clubs; Dorval; Jardins; Patrimoine

Le canal de Lachine: un paysage en constant mouvement - Paradis, Matthieu; Gelly, Alain (Histoire Québec, 2020)
Number: 4
Keywords: Lachine (canal); Paysages

« Dear Richard...send us a few buffalo tongue »: Donald Smith's Fur Trade Contacts and Peronal Credit Networks - Hamon, Max (Montreal's Square Mile: the making and transformation of a colonial metropole, 2024)
Keywords: Autochtones; Bourgeoisie; Chemins de fer; Femmes; Fourrure; Golden Square Mile

1800 to 1830. Montréal, Building British Metropolis - Robert, Jean-Claude (Montréal Capital City. The Remarkable History of the Archaeological Site of St Anne’s Market and the Parliament of the Province of Canada, 2021)
Translators: _:n117 Translators: _:n62493
Keywords: Métropole; Port

Au croisement de la perte de mémoire et de la créativité communautaire: de nouvelles innovations dans les anciens ateliers ferroviaires de Pointe-Saint-Charles - Elliott, Andrew (Bulletin de l'AQPI, 2021)
issued: 2021-21-00
Keywords: Canadien National; Chemins de fer; Conservation; Grand Tronc; Patrimoine

Ponts et traverses de la rivière des Prairies - Tessier, Stéphane (Il était une fois... Montréal-Nord, 2020)
issued: 2020-24-00
Keywords: Ponts; Rivière des Prairies; Rivière-des-Prairies

Futur parc sur la rue Marcel-Pepin. Un lieu riche en histoire - Delagrave, Louis (Le Bulletin de la Société d'histoire Rosemont-Petite-Patrie, 2020)
Number: 1
Keywords: Chemins de fer; Hôpitaux; Itinérance; Usines Angus; Variole; Épidémies

De 1800 à 1830. Montréal, jeune métropole britannique - Robert, Jean-Claude (Montréal capitale. L'exceptionnelle histoire du site archéologique du marché Sainte-Anne et du parlement de la province du Canada, 2021)
Keywords: Métropole; Port

Building landscape narratives: the material and visual culture of bridge construction in Montreal, 1854-1930 - Braiden, Heather (Université McGill, 2021)
Keywords: Ponts; Victoria (pont)

Montréal en 1919 : industries, travail et espaces résidentiels - Girard, David (Université du Québec à Montréal, 2020)
Keywords: Tramways; Travail

MUIR, HENRIETTA LOUISE - Roome, Patricia (Dictionnaire biographique du Canada, 2023)

DUPUIS, JOSEPH-NARCISSE (Dictionnaire biographique du Canada, 2022)

Railways and the Urban Soundscape: Montreal, 1850s-1950s - Rudy, Jarrett; Fahrni, Magda; Kenny, Nicolas (Urban History Review / Revue d'histoire urbaine, 2022)
issued: 2022-21-00
Keywords: Chemins de fer; Paysages

Le boulevard Saint-Laurent et son histoire - Tessier, Stéphane (Il était un fois... Montréal Nord, 2022)
issued: 2022-24-00
Keywords: Routes; Saint-Laurent (rue)

La requalification du secteur industriel du Mile End, Montréal - Bur, Justin (Bulletin de l'AQPI, 2022)
issued: 2022-22-00
Keywords: Canadien Pacifique; Carrière; Chemins de fer; Mile End

BÉÏQUE, FRÉDÉRIC-LIGORI - Vallières, Marc (Dictionnaire biographique du Canada, 2022)

Saint-Louis-Du-Mile-End. De la campagne à la ville (Bulletin de la Société d'histoire et de généalogie du Plateau-Mont-Royal, 2023)
issued: 2023-23-00
Keywords: Chemins de fer; Institution des sourds-muets; Logement; Mile End; Soeurs de la Providence

La Petite-Bourgone: bercail de l'industrie et quartier historique multiracial de Montréal - High, Steven (Bulletin de l'AQPI, 2022)
issued: 2022-22-00
Keywords: Anglophones; Canadien National; Francophones; Grand Tronc; Lachine (canal); Montreal Rolling Mills; Noirs; Petite-Bourgogne; Quartiers; Sainte-Cunégonde

DAWSON, ARTHUR OSBORNE - Miller, Carman (Dictionnaire biographique du Canada, 2023)

Histoire des communautés noires au Québec et à Montréal (2e partie) - Tessier, Stéphane (Il était une fois... Montréal-Nord, 2020)
issued: 2020-22-00
Keywords: Chemins de fer; Musique; Noirs; Travail